Perspektif Tenaga Kesehatan Puskesmas dalam Menggunakan Sistem Informasi Manajemen Puskesmas (SIMPUS) - Fauzan Kurniawan (Jurnal Admmirasi, 2021)
The development of a Puskesmas Management Information System (SIMPUS) has a goal which is to produce a system capable of providing computer-based information needed to manage patients for health workers in puskesmas, puskesmas management, and the health department. So that the presence of SIMPUS can support better health services. However, the use of electronic medical records in management information systems is influenced by the attitude of the users of this system. This study aims to determine the behavior of health center health workers in using SIMPUS. This research is a quantitative study with a cross sectional approach using the UTAUT questionnaire on Health Center health workers in Bantul Regency. The results of this study found that the Constructive Facilitating Condition had a positive effect on the construct of Behavioral Intention with a value of 69.5%. The coefficient of the latent facilitating condition (FC) to the construct Behavior Intention (BI) in this model has the greatest value among the coefficient values of the latent variable in the relationship model between other constructs, which means that the more complete the facilities that support the use of the system, the more accepted and used by user.